The Role of Community Self-Help Communication as an Agent of Change in Village Community Empowerment in North Sumatra Province - Wahyuni Deylyana Siregar; Dewi Kurniawati; Maulana Andinata Dalimunthe (Komunikologi: Jurnal Pengembangan Ilmu Komunikasi dan Sosial, 2026)
This study aims to analyze the communication of PSM as an agent of change in empowering rural communities in North Sumatra Province, and to identify the opportunities and challenges faced in implementing its role. This study uses a qualitative approach with a constructivist paradigm. Data were obtained through in-depth interviews, observations, Focus Group Discussions (FGDs), and documentation. Research informants consisted of Structural Officials and Functional Positions of PSM selected using the snowball sampling technique. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña through the stages of data condensation, data presentation, and conclusion drawing. Data validity was tested through source triangulation. The results show that PSM communication as an agent of change is carried out through understanding information and empowerment policies, adaptation and self-learning, participatory and dialogic communication, building community trust, acting as a facilitator and social mediator, and utilizing local culture and communication technology. This study also identified opportunities and challenges faced by PSM in carrying out its role. This study concludes that PSM communication is determined by the ability to integrate participatory development communication, innovation diffusion, and community empowerment within the socio-cultural context of rural communities in North Sumatra Province. This study recommends strengthening PSM communication capacity, reducing administrative burdens, and developing communication strategies that are adaptive to the characteristics of multicultural societies.